Contribuição ao estudo fitoquímico da espécie Piper arboreum aublet (piperaceae) - Costa, Jacqueline Iris de Vasconcelos (2011)
The Piperaceae Family is made up of 14 genus and 1950 species, distributed in the tropical regions of the globe being common in Brazil, especially in the Atlantic Forest. Piper auboreum, popularly known as fruto de morcego , alecrim-de-Angola , pau-de-Angola or beto-preto , is used in popular medicine in the form of tea in order to treat rheumatisms, bronchitis, cold and other illnesses of the urinary apparatus as well as venereal diseases. Under a chemical and pharmacological point of view, only a few reports are related to this species. Among the substances isolated are N-[10-(13,14-Metylenodioxyphenyl)-7(E),9(Z)-pentadienoyl]-pyrrolidine; arboreumine; N-[10-(13,14-Metylenodioxyphenyl)-7(E)-pentaenoyl]-pyrrolidine; N-[10-(13,14-Metylenodioxyphenil)-7(E),9(E)-pentadienoyl]-pyrrolidine e o metyl-3-geranyl-4-hydroxybenzoate. In this work, the literature relates pharmacological activities such as parasite and antibiotic. Consulting the chemical data in the literature, was possible to isolate and identify, through phytochemical analysis, four compounds of Piper arboreum: four amides e two aristolactams. Through chromatography and spectroscopic experiments using infrared and 1D and 2D NMR and comparison with the literature data, the following compounds were isolated: Piplaroxide; Sintenpiridone; 3,4-Epoxy-8,9-dihydropiplartine; 8,9-Dihydropiplartine; 10-Metilamina-4-hidroxy-2,3-dimetoxyphenantrene-1-carboxylic acid-lactam e 10-Metilamina-4-hidroxy-3-metoxyphenantrene-1-carboxylic acid-lactam. All these compounds are reported for the first time in this species displaying considerable value to the chemical taxonomy of the plant.